DFSS in marketing: designing an innovative value co-creation campaign. (2015) - Potra, Sabina; Pugna, Adrian
Design for Six Sigma (DFSS) is considered an approach which generates positive quality especially for new products and services. A first time right design is a key success factor for business performance. This paper is an attempt to introduce DFSS efficiency to the marketing domain in a cross-disciplinary approach. Quality attributes influence customer engagement and adequately designed, they sustain value co-creation and innovation for business management sustainability in a global competitive marketplace. The paper discusses the real-life case when DFSS was implemented in designing a successful co-creation marketing campaign.